PENGARUH MEDIA PEMBELAJARAN POP UP BOOK TERHADAP HASIL BELAJAR SISWA KELAS III MATERI KEBERAGAMAN BUDAYA DI SDN TANJUNGSARI 1 - Ahsani, Muhammad Syahrul; Uci Ulfa Nur’afifah; Budi Sasomo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this research is to determine the effect of using pop-up book learning media on student learning outcomes in third grade at SDN Tanjungsari 1 on the topic of cultural diversity. This quantitative study applied a one-group pretest-posttest design involving 20 students as both the population and sample. Data collection was conducted using a 15-item multiple-choice test administered before and after the intervention. Validity, reliability, difficulty level, and discrimination index of the instrument were tested using SPSS 24. Data analysis involved normality testing (Shapiro-Wilk) and hypothesis testing using paired sample t-test. Results showed that student scores improved from a pretest mean of 55.25 to a posttest mean of 75.25. The paired sample t-test yielded a significance value of 0.000 < 0.05, indicating a significant effect. The study concludes that pop-up book media significantly improves student learning outcomes in the subject of Pancasila Education, particularly on the topic of cultural diversity.